Long jump drills - Lomax, T. (The Best of British Track & Field Drills Series, 2009)
Coach Terry Lomax has developed into one of the country's best jumps coaches, earning him a coaching spot on two Olympic Track and Field Teams. In this instructional DVD, Coach Lomax shares his fundamental long jump skills and long jump drills. He includes several proven progressions to help your athletes jump higher and further than they ever have before. Lomax starts with his basic continuous warm-up drills that include jogging, skipping, hoping, directional lunges and body movement exercises to help reduce the chances of injury during practice and meets. Good posture and speed are important keys to successful long jumping, and Coach Lomax discusses several of his strategies to keep your athletes running and jumping "Tall" no matter what level your jumpers are at. He takes you through the 1-, 3- and 5-step drills to get your athlete higher in the pit. He also spends time showing you the proper landing techniques and how to teach long jumpers proper landing form and thrust to add inches to their jumps. Lomax also provides you with several new methods that work on the athlete's approach and take-off, and how to correct common errors by young jlong umpers when marking their starting mark.